Alterations in rat brain proteins after desflurane anesthesia - Fütterer, Carsten Dietmar; Maurer, Martin H.; Schmitt, Anne; Feldmann, Robert Enrico; Kuschinsky, Wolfgang; Waschke, Klaus F. (Anesthesiology, 2004)
Volatile anesthetics disappear from an organism after the end of anesthesia. Whether changes of protein expression persist in the brain for a longer period is not known. This study investigates the question of whether the expression of proteins is altered in the rat brain after the end of desflurane anesthesia.Three groups (n = 12 each) of rats were anesthetized with 5.7% desflurane in air for 3 h. Brains were removed directly after anesthesia, 24 h after anesthesia, or 72 h after anesthesia. Two additional groups (n = 12 each) served as naive conscious controls, in which the brains were removed without previous anesthesia 3 or 72 h after the start of the experiment. Cytosolic proteins were isolated. A proteome-wide study was performed, based on two-dimensional gel electrophoresis and mass spectrometry.Compared with conscious controls, significant (P < 0.05) increase/decrease was found: 3 h of anesthesia, 5/2 proteins; 24 h after anesthesia, 13/1 proteins; 72 h after anesthesia, 6/4 proteins. The overall changes in protein expression as quantified by the induction factor ranged from -1.67 (decrease to 60%) to 1.79 (increase by 79%) compared with the controls (100%). Some of these regulated proteins play a role in vesicle transport and metabolism.Desflurane anesthesia produces changes in cytosolic protein expression up to 72 h after anesthesia in the rat brain, indicating yet unknown persisting effects.